Validation and authentication of education and pedagogical research (2011)
This research paper develops ideas about the meaning and processes of validation and authentication of scientific research in education and pedagogy. It presents criteria and reflections that contribute to the examination of conceptions and common research practices in the academic, disciplinary and professional fields. Core concepts such as science, scientific research, community of competent practitioners, validation and authentication are developed in an explanatory and argued manner. The presentation of the concepts emphasizes the social, public and argumentative nature of science, as a system, and scientific research, as a process. Based on the articulation of these concepts, it is argued, and concluded, that the community of competent peers is the most suitable, by nature, to validate an investigation, and that legitimacy is a gradual process, carried out by society based on limited and historically contingent interests and values. In the light of these approaches, we introduce and challenge some conceptions and existing practices in our academic environments.